Ativismo judicial e judicialização da política no Supremo Tribunal Federal: estudo de três julgados proferidos pela Corte (2008-2010). - Silva, Bianca Ribeiro da (2016)
The judicial activism and the judicialization of politics are seen as global phenomenons and are storylines for several contemporary investigations of Political Science. Typical of the expansion of the Judicial Branch, they give rise to investigations in the democratic collision. In this context, assuming a neoconstitutionalist bias with the advent of the Federal Constitution of 1988, the research sought to investigate the tensions caused between democracy and the Brazilian constitutional system itself in the activism and judicialization of politics in the Judicial Branch. Therefore, it was chosen three rulings of the Supreme Court to verify the tensions in multiple themes decided by the highest court of the country: Direct Action of Unconstitutionality nº. 3.999/DF (ruled in 2008), Popular Action nº.3.388/RR (ruled in 2009) and Interlocutory Appeal in Injunction Suspension of the Public Civil Action nº. 47/PE (ruled in 2010).The issues correspond to the loss of term for party infidelity, demarcation of the aboriginal land Raposa Serra do Sol and public health, respectively. To find possible tensions in the trial, it was visualized, at first, the theoretic contributions of substantial democracy, of Ronald Dworkin, and procedural democracy, of John Hart Ely and Jürgen Habermas. Such theories were upheld for taking into consideration the role of the Judicial Branch to rank democracy. It was also approached the theory of the legitimation government body, defended by Robert Dahl, which sustains that the judicial acting acts to legitimize acts of the dominant regime. The decisions were analyzed and, based in the theoretical scenarios presented, it was concluded that there are tension between neoconstitutionalism and democracy, caused by the activism and judicialization of politics in Brazil. However, the tensions found are understood by this study as contributing to democratic development in the country, corroborating to a substantial democracy, although active and judicialized positions must be given rise, within certain self-restraint measures.